Pengaruh Perkembangan Teknologi di Era Digital bagi Pengembangan Sumber Daya Manusia di Daerah Tertinggal di Indonesia - Habibillah, Rizki; Hadjri, Muhammad Ichsan (Penerbit Goodwood, 2023)
Purpose: The purpose of this study is to determine the relationship between technology development and human resource development in underdeveloped areas, especially in Indonesia. Methodology: This study is a literature review. The sources for this literature review are indexed journals and proceedings on Google Scholars from 2019 onwards. There was only one journal in 2019, namely, 2017. Results: With low human resources and minimal access to the internet, human resources in remote areas are threatened with being left behind in facing the changing times brought by the digital era. Limitations: This study is limited to a general overview of remote areas and the impact of existing conditions in the digital era. Contribution: This research will hopefully contribute to government policy building. By giving some views on the condition of the digital era and its impact on human resource development. This study also shows the importance of human resource development in underdeveloped areas. How good will the condition be if human resource development has been done well? This study can also serve as a reference for future research on topics related to human resource development, the digital era, and underdeveloped areas in Indonesia.